2015
DOI: 10.1364/ol.40.004110
|View full text |Cite
|
Sign up to set email alerts
|

Graphene mode-locked Cr:LiSAF laser at 850  nm

Abstract: We report, for the first time to our knowledge, a mode-locked femtosecond Cr:LiSAF laser initiated with a high-quality monolayer graphene saturable absorber (GSA), synthesized by chemical-vapor deposition. The tight-focusing resonator architecture made it possible to operate the Cr:LiSAF laser with only two 135 mW, 660 nm low-cost single-mode diode lasers. At a pump power of 270 mW, the laser produced nearly transform-limited 68 fs pulses with an average power of 11.5 mW at 850 nm. The repetition rate was arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…This work promotes the application of graphene and other layered materials in mode‐locked solid‐state lasers. Up to now, plenty of mode‐locked solid‐state lasers using layered materials such as graphene, TMDCs, and BP have been achieved, as shown in Table . It can be seen that these lasers have excellent performance in pulse width, repetition rate, and pulse energy, which is not inferior to similar lasers.…”
Section: Versatile Pulsed Lasers Using 2d Layered Materialsmentioning
confidence: 99%
“…This work promotes the application of graphene and other layered materials in mode‐locked solid‐state lasers. Up to now, plenty of mode‐locked solid‐state lasers using layered materials such as graphene, TMDCs, and BP have been achieved, as shown in Table . It can be seen that these lasers have excellent performance in pulse width, repetition rate, and pulse energy, which is not inferior to similar lasers.…”
Section: Versatile Pulsed Lasers Using 2d Layered Materialsmentioning
confidence: 99%
“…The GSA used in our experiments was prepared by chemical vapor deposition as described previously [13] and was transferred onto an infrasil substrate. As described in Ref [12], the saturation fluence and recovery time were 28 μJ/cm 2 and 1.6 ps, respectively. Furthermore, previous Raman measurements indicated that a monolayer graphene was deposited on the infrasil substrate [12].…”
Section: Experimental Details and Resultsmentioning
confidence: 99%
“…In an earlier study, pulses as short as 10 fs were generated from a Kerr-lens mode-locked Cr 3+ :LiSAF laser [11]. In our previous study, we demonstrated GSA-initiated mode locking of a Cr 3+ :LiSAF laser for the first time and generated 68-fs pulses at 850 nm [12].…”
Section: Introductionmentioning
confidence: 94%
“…For instance, A Ti: sapphire mode‐locking pulse laser was demonstrated by Baek et al, which generate ultrashort pulse of 63 fs (at 800 nm) with maximum power of 480 mW. A 68 fs laser was reported by Canbaz based on Cr:LiSAF(LiSrAlF 6 ) operating at 850 nm . On the other hand, graphene SAs have also enabled several MIR pulse lasers based on Cr 2+ doped chalcogenide crystals such as ZnS .…”
Section: Pulse Laser Generation Enabled By Sas Based On Ld Materialsmentioning
confidence: 99%